The Great Gap dan Kontribusi Islam Terhadap Pemikiran Ekonomi Modern - Ferdi Dermawan Nasution; Juliana Nasution (CV. PUSDIKRA MITRA JAYA, 2025)
Currently, Indonesia has indeed built economicfacilities and infrastructure, but in fact these buildings are fragileand porous. Once the crisis wave hit the building, everything fellapart and it took a very long time to bring it back up. In fact, other Asial countries that have the same fate as Indonesia have already emerged from the economic crisis, such as Malaysia, Thailand, South Korea and others. In this context, the Islamic economic discourse is still very relevant to be discussed more seriously, and put forward as an alternative solution to overcoming the economic crisis in Indonesia, where the majorityof the population is Muslim. In fact, recently the banking worldhas adopted the Islamic economic system without a doubt. Conventional banks, for example, which have been based on theWestern economic system, are now starting to open banks basedon other money economy systems as well as developing anIslamic economic system. It seems that a fair system which formsthe basis of Islamic economics is the main reason why this systemis increasingly in demand and developed by the (Muslim) community today. Of course, the development of an Islamic economy will face many challenges today and in the future,and will serve as a test for whether the Islamic economy is able to overcome the economic crisis in Indonesia. Muslim economists are important pioneers who have successfully transformed the Islamic economic system into the modern world. Even to be honest, Western economists have actually learned from them. They appeared when the West was still in the dark ages. This includes their economy. Moreover, the emergence of this Muslimeconomy was in the post-Greek phase and pre-Western progress. However, the thoughts of these Muslim economists experiencedperiods of disconnection from generation to generation of Muslims recently. In fact, literature that discusses Islamic economics, especially the thoughts of Muslim economists, is stillvery rare and limited in the midst of the Indonesian Muslim community. The historical aspect is no exception. This study hasa very important meaning because it will trace the historical study of economic thought in Islam which is very unfavorable because, throughout Islamic history, Muslim thinkers and leaders have developed various economic ideas in such a way thatthey are not considered. The opposition comes from Schumpeter,great gap, by saying that the source of economics is from the west.